Evaluation of a SARS-CoV-2 spike protein ectodomain subunit vaccine with a squalene emulsion adjuvant in rodents and rhesus macaques - Maxim Solomadin; Kairat Tabynov; Nikolai Petrovsky; Kaissar Tabynov (Taylor & Francis Group, 2023)
COVID-19 vaccines have played an important role in reducing the impact of the current pandemic. Previously, we developed NARUVAX-C19 vaccine based on a recombinant Wuhan spike protein extracellular domain expressed in insect cells and formulated with a squalene emulsion adjuvant (Sepivac SWE™). The current study assessed the immunogenicity, efficacy, and safety of NARUVAX-C19 vaccine in rhesus macaques and hamsters. Macaques immunized intramuscularly with two doses of NARUVAX-C19 vaccine showed no adverse effects and demonstrated cellular immunity as assessed by T cell IFN-γ responses against spike protein, in addition to inducing a humoral response. Serum from immunized animals neutralized the homologous wild-type SARS-CoV-2 virus as well as the Alpha and Delta variants. In hamsters, immunization with NARUVAX-C19 vaccine protected against a heterologous challenge with the Delta virus, as reflected by reduced lung and nasal viral loads and lung pathology in immunized animals. Nevertheless, some NARUVAX-C19 vaccinated animals were still shown to transmit infection to naïve sentinel animals. Overall, NARUVAX-C19 vaccine induced broadly cross-neutralizing antibody and T cell IFN-γ responses in rhesus macaques and provided heterologous protection of hamsters against infection by the Delta virus variant. This data supports the utility of squalene emulsion-based adjuvanted recombinant vaccine in protection against SARS-CoV-2 and supports their continued clinical development.